Simplified environmental assessment in an urban stream in the Veado stream waterbasin in Presidente Prudente - SP - Barbosa, Eliane Baptista; Tamagno, Gabriel Itada; Romero, Danielli Cristina Granado; Okimoto, Fernando Sérgio (National Journal of City Management, 2025)
Objective - To analyze the environmental integrity of the Vale do Sol Stream in a single visit, in the municipality of Presidente Prudente/SP. Methodology - Application of a rapid assessment protocol and the analysis of some limnological parameters. The RAP was applied at three stations along the stream, and the following parameters were evaluated: type of bank occupation; streambed siltation; presence of waste; water odor; presence of substances in the water; water transparency; bottom type; diversity of bottom habitats; substrate types; water surface condition; alterations in the river channel; bank stability; presence of riparian vegetation; extent of the Permanent Preservation Area (PPA); and presence of aquatic plants. For water quality assessment, the parameters of electrical conductivity, dissolved oxygen, pH, temperature, and turbidity were analyzed. Originality/Relevance - The Rapid Assessment Protocol (RAP), despite being a consolidated methodology in the academic and scientific community, has been explored little. Its ease of use, low technological cost, and precision allow for robust environmental analyses. Furthermore, the use of limnological analysis to corroborate the RAP strengthens the relevance and scientific innovation of the work. Results - The environment is anthropized, but the presence of surrounding vegetation contributes to the water meeting conditions in compliance with the limits established by CONAMA Resolution No. 357/2005 for the parameters studied. Theoretical/Methodological Contributions - The study reflects the conditions of the analyzed stream, but it also reflects the vast majority, if not all, of urban water bodies. The analyses performed, being simple, facilitate their use by municipal and water management agencies. Social and Environmental Contributions - The methodology itself allows for an understanding of the important variables for maintaining or restoring the environment adjacent to water bodies, promoting the awareness and consciousness necessary for proactive actions and positive environmental impacts.